Role of hydrogen spillover in methanol synthesis over Cu/ZrO2 - Jung, KD; Bell, AT (ACADEMIC PRESS INC, 2000)
Recent studies have shown that the synthesis of methanol from both CO and CO2 over Cu/ZrO2 involves the spillover of H atoms formed on Cu to the surface of ZrO2. The atomic H then participates in the hydrogenation of carbon-containing species (i.e., HCOO-Zr and HCO3-Zr) to methanol. The present study examines the dynamics of H/D exchange of HO-Zr, HCOO-Zr, and CH3O-Zr groups present on the surface of ZrO2 and Cu/ZrO2 by means of in situ infrared spectroscopy. The rate of H/D exchange of HO-Zr groups is much more rapid in the presence than in the absence of Cu dispersed on the surface of ZrO2. This effect is attributed to the higher effectiveness of Cu to dissociate H-2(D-2). While adsorbed water significantly inhibits the rate of H/D exchange on ZrO2, the opposite effect is observed for Cu/ZrO2. The reason is that adsorbed water inhibits the dissociation of H-2(D-2) on the surface of ZrO2 but not on the surface of Cu. Adsorbed water facilitates the transport of H(D) atoms formed on the surface of Cu across the surface of ZrO2 as a consequence of hydrogen bonding between adsorbed H2O and HO-Zr groups. Formate groups are formed on the surface of ZrO2 primarily via the process CO(g) + HO-Zr --> HCOO-Zr. Formate groups can also form on the surface of Cu and spill over onto the surface of ZrO2. The presence of formate groups inhibits the rate of H/D exchange of HO-Zr groups. H/D exchange of HCOO-Zr is also observed but occurs at a slower rate than the isotopic exchange of HO-Zr groups. As in the absence of formate groups, adsorbed water inhibits the rate of HID exchange for ZrO2 but enhances it for Cu/ZrO2. The dynamics of H/D exchange are compared with the dynamics of methanol formation as measured by the rate of CH3O-Zr formation on Cu/ZrO2. On the basis of this analysis it is concluded that the rate of hydrogen spillover from Cu is more than an order of magnitude faster than the rate of methanol formation, and, hence, not a rate-limiting step in the synthesis of methanol over Cu/ZrO2. (C) 2000 Academic Press.
Keywords: COPPER-ZIRCONIA CATALYSTS; TEMPERATURE-PROGRAMMED DESORPTION; CARBON-DIOXIDE; AEROGEL CATALYSTS; SYNTHESIS MECHANISM; CU-ZRO2 CATALYSTS; CO2 HYDROGENATION; ADSORPTION; SURFACE; CU/SIO2